Accurate DC offset calibration of Doppler radar via non‐convex optimisation. Issue 16 (1st August 2015) - Zhao, Heng; Hong, Hong; Sun, Li; Xi, Feng; Li, Changzhi; Zhu, Xiaohua
Abstract : Continuous‐wave Doppler radar has attracted a lot of attention for non‐contact vital sign detection. In the typical quadrature homotype architecture, the DC offset is a tough issue in that it seriously deteriorates the demodulated results. However, existing methods for DC offset calibration can hardly obtain accurate compensation, especially when the sparsity of measurement outliers is relatively large. Proposed is a novel iteratively reweighed ℓ1 algorithm‐based error correction method. Simulated and experimental results demonstrate the advantages of the method for accurate DC offset calibration.